Evolutionary origin of the frameshift sites in the ribosomal frameshifting genes of Euplotes - Ruan-lin Wang; Xiao-yan Liu; Qing-yao Meng; Xin Zhang; Yue-jun Fu; Ai-hua Liang (BMC Genomics)
Abstract Background Programmed ribosome frameshifting is a translational recoding event in which ribosomes slip forward or backward along the mRNA. Although genes utilizing programmed ribosomal frameshifting for their expression have been found in most organisms, such genes are commonly considered rare. However, previous studies indicated that both +1 and +2 ribosomal frameshifting are frequently required for the expression of genes in the ciliates Euplotes. In this study, we explored the possible evolutionary origin of the frameshift sites by comparative transcriptome and genome analyses. Results We sequenced the transcriptomes of different Euplotes octocarinatus strains and performed comparative analyses of the frameshift sites. Finally, a total of 147 non-conserved frameshift sites among different strains were identified. Multiple sequence alignment results showed that +1 frameshift sites could be generated by random single-nucleotide insertion and +2 frameshift sites could be generated by insertion of ‘TA’ or single-nucleotide deletion. In addition, frameshift sites tend to be less frequent in highly expressed genes. The distances between indel sites and frameshift sites were generally short. And the changed amino acids numbers of the indel sites located inside the protein domain were significantly less than that of the indel sites located outside the domain. Furthermore, we also found a putatively newly formed frameshift site which exists only in the macronucleus but not in the micronucleus of Euplotes woodruffi. Conclusions We provide an overview of the evolutionary origin of frameshift sites in Euplotes. Our results suggest that the widespread ribosomal frameshifting in Euplotes may be a result of long-term accumulation of indel mutation. And preservation of these indel mutations in the genome of Euplotes apparently need to meet some constraints.